Inter-region relative price convergence in Korea - Seongman Moon (East Asian economic review, 2017)
This paper examines the persistence of relative consumer price indices for 15 regions in Korea including 6 metropolitan cities and 9 provinces over the period of 1990-2016. In particular, we ask if relative regional price indices contain a common stochastic trend and find that they are not. We then investigate how quickly these relative prices converge to their long run value and find that a half-life of a deviation from the long run value is in the range of 13 to 22 months for the aggregate consumer price indices and in the range of 7 to 13 months for the tradable goods price indices, which is much quicker than the estimates of previous studies. These estimates suggest that existing monetary models with the realistic duration of price rigidities can generate the persistence in relative price indices.
10.11644/KIEP.EAER.2017.21.2.326; 10.11644/KIEP.EAER.2017.21.2.326; 2862898-6; 2508-1667; East Asian economic review; 863610854